Subtitusi Ubi Ungu (Ipomoea batatas) pada Cake Coklat dengan Puding Agar Karakter Sebagai Dekorasi - Luthfiah Luthfiah; Adilham Adilham; Rahmawati Saleh; Fifi Arfini (Lembaga Pengembangan Kinerja Dosen, 2025)
Cake is a wheat flour-based food product that is popular because of its sweet taste, soft texture, and attractive appearance. This study aims to evaluate the effect of purple sweet potato (Ipomoea batatas) paste substitution on the sensory, chemical, and physical quality of chocolate cake decorated with character pudding. The study was conducted in May–August 2025 at the Makassar Health Laboratory Center and the Chemistry Laboratory of the Pangkep State Agricultural Polytechnic. The study design used a Completely Randomized Design (CRD) with five treatments of purple sweet potato paste concentration (0%, 10%, 20%, 30%, 40%) and two replications. The parameters analyzed included sensory tests (color, aroma, taste, texture, and overall), chemical tests (antioxidant activity, water content, protein, fat, ash, and carbohydrate), and physical tests (expandability and crumb morphology). Data were analyzed using ANOVA and Duncan's further test for parameters with significant differences. The results showed that the addition of purple sweet potato paste had a significant effect (p < 0.05) on sensory and chemical characteristics. Treatment A4 (40% purple sweet potato paste) obtained the highest score in the hedonic test with an average panelist preference level of 4 (like). The best chemical characteristics were also obtained in A4, namely antioxidant content of 25.6%, water content of 32.97%, protein 3.52%, fat 17.19%, ash 1.34%, and carbohydrate 45.05%. Physically, the rise power was not significantly different between treatments, but the crumb morphology showed pore irregularities at high concentrations.